Compute -47+69i/7+6i where i = sqrt(-1). Express your answer in the form a+bi, where a and b are real numbers.

mingus Sep 16, 2023

#2**-2 **

We can simplify it as follows:

\[

-47 + \frac{69i}{7} + 6i = -47 + \frac{69i + 42i}{7} = -47 + \frac{101i}{7}.

\]

Now, we can express it in the form \(a + bi\), where \(a\) and \(b\) are real numbers:

\[

-47 + \frac{101i}{7} = -\frac{319}{7} + \frac{101}{7}i.

\]

So, the expression \(-47 + \frac{69i}{7} + 6i\) in the form \(a + bi\) is \(-\frac{319}{7} + \frac{101}{7}i\), where \(a = -\frac{319}{7}\) and \(b = \frac{101}{7}\).

HolaHola Sep 16, 2023